2021
DOI: 10.5194/acp-21-7135-2021
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of organosulfates with water vapor under sub- and supersaturated conditions

Abstract: Abstract. Organosulfates (OSs) are important constituents of secondary organic aerosols, but their hygroscopic properties and cloud condensation nucleation (CCN) activities have not been well understood. In this work we employed three complementary techniques to characterize interactions of several OSs with water vapor under sub- and supersaturated conditions. A vapor sorption analyzer was used to measure mass changes in OS samples with relative humidity (RH, 0 %–90 %); among the 11 organosulfates examined, on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…𝜅𝜅 𝑖𝑖𝑖𝑖𝑖𝑖 = 𝜅𝜅 𝑅𝑅𝑇𝑇 = 0.604 for ammonium sulfate (Rose et al, 2008). The intrinsic and experimentally derived 165 values also agree well for water-soluble compounds and partially soluble organics (Dawson et al, 2020;Peng et al, 2021Peng et al, , 2022.…”
Section: Theory and Analysissupporting
confidence: 64%
“…𝜅𝜅 𝑖𝑖𝑖𝑖𝑖𝑖 = 𝜅𝜅 𝑅𝑅𝑇𝑇 = 0.604 for ammonium sulfate (Rose et al, 2008). The intrinsic and experimentally derived 165 values also agree well for water-soluble compounds and partially soluble organics (Dawson et al, 2020;Peng et al, 2021Peng et al, , 2022.…”
Section: Theory and Analysissupporting
confidence: 64%
“…Surface tension reduction in water solution caused by atmospheric surfactants were observed frequently in previous studies (Facchini et al, 1999;Gerard et al, 2016). Results have showed that neglect of surface tension reduction may lead to higher CCN values than Chem or growth factor derived GF (Irwin et al, 2010;Wu et al, 2013;Zhao et al, 2016;Hu et al, 2020;Peng et al, 2021), as well as underpredictions of CCN number concentration (Good et al, 2010;Asa-Awuku et al, 2011;Ovadnevaite et al, 2017;Cai et al, 2020). Hu et al (2020) reported that Chem underpredicted CCN by 13% and 18% at supersaturation ratios of 0.1% and 0.3%, which may be attributed to the depression of droplet surface tension by potential surface-active organics.…”
Section: Closure Study Between Ccn and Chemmentioning
confidence: 90%
“…SO 4 •– radicals have been recognized as a potentially important source of surface-active organosulfates (OSs) in the environment, 7 10 which can modify aerosol cloud interactions. 11 , 12 A large variety of OSs have been identified in both field and laboratory studies, several of which are proposed to only be formed from SO 4 •– radicals. 9 , 13 17 The SO 4 •– radical is thought to be formed primarily in the autoxidation of SO 2 ; however, it can also be formed from the activation of sulfate and bisulfate anions with OH, NO 3 , 4 and to a small extent ferric ion complexes.…”
Section: Introductionmentioning
confidence: 99%
“…•− radicals have been recognized as a potentially important source of surface-active organosulfates (OSs) in the environment, 7−10 which can modify aerosol cloud interactions. 11,12 A large variety of OSs have been identified in both field and laboratory studies, several of which are proposed to only be formed from SO 4…”
Section: ■ Introductionmentioning
confidence: 99%